Determinants of HIV infection among children born to HIV positive mothers on prevention of mother to child transmission program at referral hospitals in west Amhara, Ethiopia; case control study - Asrat Alemu; Wondwosen Molla; Kindu Yinges; Muhabaw Shumye (BMC, 2022)
Abstract Background Human Immune Deficiency Virus infection among children has continued to be a global concern with an estimated 160,000 new infections in 2018. Over 90% acquire HIV from their mother. Currently, 92% of pregnant women are on antiretroviral therapy (ART). Despite, greater achievements in coverage of PMTCT and ARV drug in Ethiopia as well as in west Amhara, child HIV infections are yet an important public health problem with a high transmission rate. There are limited studies done in Ethiopia on identifying determinants of child HIV infection. Objective This study was aimed at identifying determinants of HIV infection among children born to HIV positive mothers on the PMTCT program at referral hospitals in the west Amhara, Ethiopia, 2021. Methods An unmatched case-control study was conducted at referral hospitals in the west Amhara region, Ethiopia. Data were collected through document review, which has been registered from July 1, 2016 to July 1, 2020. A two-stage sampling technique was applied. Consecutive sampling technique for cases and simple random sampling technique for controls was done to include a total of 320 samples (66 cases and 254 controls). Epi data 4.6 for data entry and SPSS 23 for analysis were used. Variables with p- value ≤0.2 in bivariate regression were run in the multivariable logistic regression and AOR with 95% CI and a p-value ≤0.05 was used to declare determinants. Result Home delivery (AOR = 4.3; 95%CI: 2.0, 11.6), mixed feeding (AOR = 10; 95%CI: 3.2, 17.9), poor maternal ARV drug adherence (AOR = 4.3; 95% CI: 1.4, 13.4), advanced WHO clinical stage (AOR = 11.4; 95% CI: 4.1,19.1), poor nevirapine adherence (AOR = 10; 95% CI: 3.2, 22.4) and late enrollment of the infant (AOR = 15; 95% CI: 3.0, 3.0,20.5) were determinants. Conclusion Minister of Health and NGOs should work on mobilization of the community and awareness creation on the important of exclusive breast feeding, drugs adherence, on benefit of health institutional delivery as well as the risk of homedelivery.